Pediatric neurosurgical-oncology scope and management paradigms in Sub-Saharan Africa: a collaboration among 7 referral hospitals on the subcontinent - Haizel-Cobbina, Joseline; Chotai, Silky; Labuschagne, Jason; Belete, Addisalem; Ashagere, Yordanos; Shabani, Hamisi K.; Copeland, William; Sichizya, Kachinga; Ahmad, Misbahu Haruna; Nketiah-Boakye, Frank; Dewan, Michael C. (Frontiers in Oncology, 2023)
Understanding of the epidemiology and biology of pediatric CNS tumors has advanced dramatically over the last decade; however there remains a discrepancy in the understanding of epidemiologic data and clinical capacity between high and lower income countries.We collected and analyzed hospital-level burden and capacity-oriented data from pediatric neurosurgical oncology units at 7 referral hospitals in Sub-Saharan Africa (SSA).A cross sectional epidemiological survey was conducted using REDCap at the 7 SSA sites, capturing 3-month aggregate data for patients managed over a total of 9 months. Descriptive statistical analyses for the aggregate data were performed.Across the neurosurgical spectrum, 15% of neurosurgery outpatient and 16% of neurosurgery operative volume was represented by pediatric neuro-oncology across the 7 study sites. Eightysix percent and 87% of patients who received surgery underwent preoperative CT scan and/or MRI respectively. Among 312 patients evaluated with a CNS tumor, 211 (68%) underwent surgery. Mean surgery wait time was 26.6 ± 36.3 days after initial presentation at the clinic. The most common tumor location was posterior fossa (n=94, 30%), followed by sellar/suprasellar region (n=56, 18%). Histopathologic analysis was performed for 189 patients (89%). The most common pathologic diagnosis was low grade glioma (n=43, 23%), followed by medulloblastoma (n=37, 20%), and craniopharyngioma (n=31, 17%). Among patients for whom adjuvant therapy was indicated, only 26% received chemotherapy and 15% received radiotherapy.The histopathologic variety of pediatric brain and spinal tumors managed across 7 SSA referral hospitals was similar to published accounts from other parts of the world. About two-thirds of patients received a tumor-directed surgery with significant inter-institutional variability. Less than a third of patients received adjuvant therapy when indicated. Multi-dimensional capacity building efforts in neuro-oncology are necessary to approach parity in the management of children with brain and spinal tumors in SSA.